Pengembangan aplikasi “CPA” (Covid-19 prevention application) sebagai literasi mitigasi bencana covid-19 bagi siswa SMP - Alifian Nabila; Neni Wahyuningtyas; Agung Wiradimadja (JINoP (Jurnal Inovasi Pembelajaran), 2021)
The Covid-19 pandemic has brought major changes, including education where most learning activities are conducted online. It is thus necessary to adapt into online learning policies where innovation is urgently needed. Among the innovations is an e-book titled Covid-19 Prevention Application (CPA) that contains Covid-19 disaster mitigation literacy for students. This research aims to: 1) produce an app for CPA; and 2) test the feasibility level of CPA app as a learning resource. The material in CPA app relates to disaster mitigation, linked to the Social Studies Learning for junior high schools, namely Social Change for the 9th graders (Class IX.1) at SMPN 21 Malang. This research and development modified Borg & Gall model, which is relevant to constructivism learning theory, Edgar Dale’s theory of experience, and cybernetic learning theory. Results show that the development of the CPA app is “highly feasible”. This result implied that CPA app offers solutions to help students in mitigating the Covid-19 disaster through creative learning. It is suggested that further large-scale trials will be conducted in the future to measure the level of effectiveness.